Characterisation of Indian jujube (Ziziphus mauritiana Lamk.) germplasm under semi-arid conditions (Indian Journal of Arid Horticulture, 2025)
A comprehensive characterization of 28 germplasm of Indian jujube (Ziziphus mauritiana Lamk.) was conducted for morphological traits of fruit and stone. Significant variability was observed in fruit shape apex and fruit colour at maturity. Twelve germplasm had round fruit apex and eleven germplasm exhibited pointed fruit apex, rest five showed flat apex of fruit. Fruit skin colour like yellow, light yellow, yellowish green, greenish yellow, light green with yellow shade, greenish, green, pale green, light green and mixture of greenish to yellowish was recorded. Most of germplasm (16) exhibited ridged and wart fruit surface and remaining had plain fruit surface. Germplasm Dandan, Safeda Selection, Rohtak Safeda, Seo, Hsaianaul, Katha Bombay, Thornless, Sanori and Kaithali had soft pulp texture whereas; Bawal Selection 1 and Umran had hard pulp texture. Remaining germplasm were grouped in medium soft pulp texture. Stone shapes further classified into oblong, oval, spindle, club, and falcate categories along with stone shape apex. Further the selected germplasm grouped as per DUS guidelines. Based on fruit shape, the maximum germplasm (10) fell in group of ovate fruit shape, followed by oval (eight germplasm) and had falcate (one germplasm). Similarly for pulp texture, most of germplasm (17) were grouped in medium pulp texture fruit. The two germplasm were grouped under hard pulp texture and rest of nine germplasm had soft pulp texture. Stone shape of fourteen germplasm fell in oval shape group, followed by club shape (five germplasm) and falcate, spindle, oblong group contain three germplasm in each. Wide variability was observed in various morphological traits and suggests differences in the evolutionary origins of these cultivars within the species.